Pengaruh Struktur Good Corporate Governance Terhadap Tax Avoidance - Yeni Cristan; Poniman Poniman (Owner : Riset dan Jurnal Akuntansi, 2023)
P Taxes are the largest income in Indonesia, but there are still many tax-payer who are negligent in fulfilling their tax obligations. The companies think that high tax payments reduce operating profits and hinder the development of the company. Company managers often commit fraud in order to get large profits, which is why corporate governance is very necessary in controlling the company. This research was conducted to test the effect of Good Corporate Governance to Tax Avoidance. The independent variables in this study were proxied from Good Corporate Governance which include Managerial Ownership, Institutional Ownership, Board of Independent Commissioners and Audit Committee, while the dependent variable is Tax Avoidance which measured by Effective Tax Rate. This research used a quantitative approach with associative form to determine the correlation between variables. The population of this study is consumer goods industry sector company listed on Indonesia Stock Exchange for 2017-2021 period.  The sampling technique used is purposive sampling, where samples of 14 companies were collected within five years,and obtain 62 samples after outlier. The data analysis methods used are descriptive statistical tests, classical assumption tests, multiple linear regression analysis and hypothesis tests. The results showed that Managerial Ownership, Institutional Ownership and Audit Committee partially did not significantly effect Tax Avoidance, while the Board of Independent Commissioners had a significant negative effect on Tax Avoidance. Managerial Ownership, Institutional Ownership, Board of Independent Commissioners and Audit Committee simultaneously do not effect Tax Avoidance.